An epidemiological assessment of the effect of ambient temperature on the incidence of preterm births: Identifying windows of susceptibility during pregnancy. (May 2018) - Zheng, Xiangrong; Zhang, Weishe; Lu, Chan; Norbäck, Dan; Deng, Qihong
Abstract: It is well known that exposure to thermal stress during pregnancy can lead to an increased incidence of premature births. However, there is little known regarding window(s) of susceptibility during the course of a pregnancy. We attempted to identify possible windows of susceptibility in a cohort study of 3604 children in Changsha with a hot-summer and cold winter climatic characteristics. We examined the association between PTB and ambient temperature during different timing windows of pregnancy: conception month, three trimesters, birth month and entire pregnancy. We found a U-shaped relation between the prevalence of PTB and mean ambient temperature during pregnancy. Both high and low temperatures were associated with PTB risk, adjusted OR (95% CI) respectively 2.57 (1.98–3.33) and 2.39 (1.93–2.95) for 0.5 °C increase in high temperature range (>18.2°C) and 0.5°C decrease in low temperature range (< 18.2°C). Specifically, PTB was significantly associated with ambient temperature and extreme heat/cold days during conception month and the third trimester. Sensitivity analysis indicated that female fetus were more susceptible to the risk of ambient temperature. Our study indicates that the risk of preterm birth due to high or low temperature may exist early during the conception month. Graphical abstract: fx1 Highlights: Long-term effect of ambient temperature on preterm birth (PTB) is unclear. We examined the association between PTB and ambient temperature during different timing windows. We observed U-shaped relation between ambient temperature and PTB. Both high and low temperatures and extreme heat and cold days increased PTB risk. PTB risk was found to be associated with ambient temperature exposure during conception month.